The geography of nature access opportunities - Knight, Jonathan E. (Kansas State University, 2012)
Experiences in natural environments are perceived as a human necessity. Additionally, prior studies show that nature access has emotional, cognitive, and psychological benefits for children. Nature is defined as a space comprised mostly of vegetation that allows an individual to escape common surroundings. Access is defined as the ability to interact with high-quality nature by walking or biking in close proximity to one’s place of residence. This geospatial analysis employs Geographic Information Systems (GIS) technology and site analysis to assess whether or not socioeconomic factors, and their relationship to housing choice, affect a child’s access to nature. The study includes measures of socioeconomic status and how these factors influence a child’s access to nature within parks and school facilities. The results show that including qualitative factors enhances the traditional model of measuring “distance as access.” There was no inequality in access found in the study area when qualitative factors are included. The project implication is that communities can focus public resources and planning efforts in areas lacking access to nature for children. This leads to geographically less segregated neighborhoods and improved equity in nature access across a community.
Keywords: Equity; Access; Geographic Information Systems; Childhood development; Parks; Schools; Area Planning and Development (0341); Recreation and Tourism (0814); Urban Planning (0999)